2000
DOI: 10.1016/s0042-6989(99)00244-8
|View full text |Cite
|
Sign up to set email alerts
|

The psychophysics of visual search

Abstract: Most theories of visual search emphasize issues of limited versus unlimited capacity and serial versus parallel processing. In the present article, we suggest a broader framework based on two principles, one empirical and one theoretical. The empirical principle is to focus on conditions at the intersection of visual search and the simple detection and discrimination paradigms of spatial vision. Such simple search conditions avoid artifacts and phenomena specific to more complex stimuli and tasks. The theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
476
5
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(517 citation statements)
references
References 147 publications
28
476
5
1
Order By: Relevance
“…In particular, it is only a complete summary of performance if the shape of the psychometric functions is consistent over all of the conditions of interest. The slope of these functions do vary with set size (e.g., Palmer et al, 2000). This effect is not large, but it introduces a complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is only a complete summary of performance if the shape of the psychometric functions is consistent over all of the conditions of interest. The slope of these functions do vary with set size (e.g., Palmer et al, 2000). This effect is not large, but it introduces a complication.…”
Section: Discussionmentioning
confidence: 99%
“…We follow the notation commonly used in signal detection theory (D. M. Green & Swets, 1966; for more detail, see Palmer et al, 2000). The representation of each stimulus corresponds to a real-valued random variable.…”
Section: Common Notation and Assumptionsmentioning
confidence: 99%
“…Perhaps object recognition is accomplished by a parallel process that is capable of processing many items at once. Different types of parallel process can be devised that will produce the same patterns of data that led Treisman and others to propose a serial selfterminating search [13].…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%
“…The importance of stimulus discriminability is well established in the visual search literature and has been incorporated into major theoretical frameworks of visual search (e.g., Duncan & Humphreys, 1989;Palmer, Verghese, & Pavel, 2000;Treisman, 1991;Wolfe, Cave, & Franzel, 1989;Wolfe, 1994). Numerous previous studies have demonstrated that detecting a search target becomes more difficult with increased similarity (i.e., lower discriminability) between the target item and the distractors (e.g., Nagy & Sanchez, 1990;Neisser, 1967;Pashler, 1987;Rayner & Fisher, 1987).…”
Section: Current Studymentioning
confidence: 99%